Alterations in mucosa branched N-glycans lead to dysbiosis and downregulation of ILC3: a key driver of intestinal inflammation - Cláudia S. Rodrigues; Joana Gaifem; Márcia S. Pereira; Maria Francisca Alves; Mariana Silva; Nuno Padrão; Bruno Cavadas; Catarina Moreira-Barbosa; Inês Alves; Ricardo Marcos-Pinto; Joana Torres; Aonghus Lavelle; et al. (Gut Microbes)
The perturbation of the symbiotic relationship between microbes and intestinal immune system contributes to gut inflammation and Inflammatory Bowel Disease (IBD) development. The host mucosa glycans (glycocalyx) creates a major biological interface between gut microorganisms and host immunity that remains ill-defined. Glycans are essential players in IBD immunopathogenesis, even years before disease onset. However, how changes in mucosa glycosylation shape microbiome and how this impact gut immune response and inflammation remains to be clarified. Here, we revealed that alterations in the expression of complex branched N-glycans at gut mucosa surface, modeled in glycoengineered mice, resulted in dysbiosis, with a deficiency in Firmicutes bacteria. Concomitantly, this mucosa N-glycan switch was associated with a downregulation of type 3 innate lymphoid cells (ILC3)-mediated immune response, leading to the transition of ILC3 toward an ILC1 proinflammatory phenotype and increased TNFα production. In addition, we demonstrated that the mucosa glycosylation remodeling through prophylactic supplementation with glycans at steady state was able to restore microbial-derived short-chain fatty acids and microbial sensing (by NOD2 expression) alongside the rescue of the expression of ILC3 module, suppressing intestinal inflammation and controlling disease onset. In a complementary approach, we further showed that IBD patients, often displaying dysbiosis, exhibited a tendency of decreased MGAT5 expression at epithelial cells that was accompanied by reduced ILC3 expression in gut mucosa. Altogether, these results unlock the effects of alterations in mucosa glycome composition in the regulation of the bidirectional crosstalk between microbiota and gut immune response, revealing host branched N-glycans/microbiota/ILC3 axis as an essential pathway in gut homeostasis and in preventing health to intestinal inflammation transition.